Social factors for coastal management: a short review and some insights - Chee, Kong Yap; Chee, Seng Leow (RAFT Publications, 2019)
Integration of social-economic and environmental perspectives are important in making the goal of coastal management to be obtained within expectation. In this review paper, the social factor is focused upon in particular. This is due to the fact that human cannot escape from surrounding which becomes their habitat niche. From this review, the social factors are known as 1) human attitudes, 2) differences of social-cultural values, ethics and classes, 3) population growth, 4) stakeholder/citizen perceptions, 5) involvement of social/public community, 6) anthropogenic activities, and 7) the involvement of managers and governance. Most dominantly, anthropogenic activities involved aquaculture, fishing, shipping and port activities, sediment mining, salt extraction, and tourism.